Ewe size and nutrition during pregnancy : effects on metabolic and productive performance of the offspring : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Turitea, Palmerston North, New Zealand - Linden, Danitsja Stephanie van der (Massey University, 2010)
Exposure of the fetus to adverse conditions in utero may result in developmental adaptations that alter metabolism and postnatal growth of the offspring. This thesis investigated the effects of dam size and nutrition during pregnancy on growth, metabolic function and lactational and productive performance of the female offspring to two years of age. Four-hundred and fifty heavy (60.8 kg ± 0.18) and 450 light (42.5 kg ± 0.17) dams were randomly allocated to ad libitum or maintenance nutritional regimens from days 21 - 140 of pregnancy, under pastoral grazing conditions. From one week prior to lambing, all dams were fed ad libitum until weaning. After weaning, female progeny were managed and fed under pastoral conditions as one group. Maternal nutrition during pregnancy affected lamb growth to weaning, however, after weaning lamb growth was affected by dam size. Dam size had no effect on glucose metabolism, adrenal function or fat metabolism in 16-month-old female twin offspring. Dam nutrition during pregnancy had a minor effect on glucose metabolism and no effect on adrenal function or lipolysis, however, it did possibly affect gluconeogenesis and/or glycogenolysis, with increased glucose production in ewes born to maintenance-fed dams. Ewes born to dams fed maintenance showed greater milk production, lactose percentage, lactose and crude protein yield. Ewes born to heavy dams showed greater milk production and lactose yield. Dam size had no effect on reproductive performance of the female offspring. Being born to a larger dam showed no advantages over being born to smaller dams, for number of lambs born and weight of lambs at birth and weaning. ‘Grand’dam maintenance nutrition increased lamb birth and weaning weight and lamb growth rates of the ‘grand’offspring. Ewes born to maintenance-fed dams could have an advantage over ewes born to ad libitum-fed dams in physiological stressful situations in life as their liver may be able to supply more glucose to support their growing conceptus and milk production to increase the chances of survival of their offspring. These results indicate that it is possible to programme the offspring by feeding their dams differently during pregnancy under grazing conditions. With a better understanding of how offspring can be programmed through different maternal nutritional regimens, it may be possible to significantly increase the production potential of the New Zealand ewe population.
Keywords: Sheep reproduction; Lamb metabolism; Maternal nutrition; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300400 Animal Production::300403 Animal nutrition